“That Time of Month:” Premenstrual Dysphoric Disorder in the Criminal Law-Another Look - Langer, Rosanna (2012)
Abstract: This paper argues that women suffering from pre-menstrual dysphoric disorder (PMDD) ought to have available to them a range of legal defences that accurately reflect culpability. As PMDD focuses primarily on emotional mood and behavioural symptoms as opposed to physical manifestations of the premenstrual period, legal treatment of PMDD can be usefully compared to other “disordered states“ that affect mental capacity, rationality and intent. Evolution of PMDD as a distinctive form of psychiatric disorder warrants a new consideration of the dual feminist concerns about the invisibility of women in criminal law theory and the undue labeling of all women. This article considers the application of criminal law defenses in light of newer research characterizing pre-menstrual mental disorder as a dynamic psychiatric and physiological state with shifting determinants that may be experienced differently over time. Ultimately, criminology must grapple with developing an account of women's criminality that reflects accurately women's lives lived within the sometimes overwhelming experience of biopsychosocial stressors. Reviewing PMDD in light of these concerns supports an enhanced understanding of the dynamics between women's mental health and culpability